Changing Men: Integrating Freirian Education, Human Relations Training, and Anti-Oppression Education in a Men’s Transformational Learning Experience - Steven A. Schapiro (Adult Education Research Conference, 2007)
This paper presents a model of a pedagogy for anti-sexist education for men, drawing on and integrating principles and practices from the three approaches noted in the title, and adapting Kegan’s conceptualization of the various kinds of learning (or holding) environments necessary to support developmental change.